First Randomized, Multicenter, Placebo-Controlled Study of Self-Administered Intranasal Etripamil for Acute Conversion of Spontaneous Paroxysmal Supraventricular Tachycardia (NODE-301). (28th November 2022) - Stambler, Bruce S.; Plat, Francis; Sager, Philip T.; Shardonofsky, Silvia; Wight, Douglas; Potvin, Diane; Pandey, A. Shekhar; Ip, James E.; Coutu, Benoit; Mondésert, Blandine; Sterns, Laurence D.; Bennett, Matthew; et al.
Abstract : Background: Pharmacologic termination of paroxysmal supraventricular tachycardia (PSVT) often requires medically supervised intervention. Intranasal etripamil, is an investigational fast-acting, nondihydropyridine, L-type calcium channel blocker, designed for unsupervised self-administration to terminate atrioventricular nodal–dependent PSVT. Phase 2 results showed potential safety and efficacy of etripamil in 104 patients with PSVT. Methods: NODE-301, a phase 3, multicenter, double-blind, placebo-controlled study evaluated the efficacy and safety of etripamil nasal spray administered, unsupervised in patients with symptomatic sustained PSVT. After a medically supervised etripamil test dose while in sinus rhythm, patients were randomized 2:1 to receive etripamil 70 mg or placebo. When PSVT symptoms developed, patients applied a cardiac monitor and attempted a vagal maneuver; if symptoms persisted, they self-administered blinded treatment. An independent Adjudication Committee reviewed continuous electrocardiogram recordings. The primary efficacy endpoint was termination of adjudicated PSVT within 5 hours after study drug administration. Results: NODE-301 accrued 156 positively adjudicated PSVT events treated with etripamil (n=107) or placebo (n=49). The hazard ratio for the primary endpoint, time-to-conversion to sinus rhythm during the 5-hour observation period, was 1.086 (95% CI, 0.726–1.623; P =0.12). In predefined sensitivity analyses, etripamil effects (compared with placebo) occurred at 3, 5, 10, 20, and 30 minutes ( P <0.05). For example, at 30 minutes, there was a 53.7% of SVT conversion in the treatment arm compared to 34.7% in the placebo arm (hazard ratio, 1.87 [95% CI, 1.09–3.22]; P =0.02). Etripamil was well tolerated; adverse events were mainly related to transient nasal discomfort and congestion (19.6% and 8.0%, respectively, of randomized treatment-emergent adverse events. Conclusions: Although the primary 5-hour efficacy endpoint was not met, analyses at earlier time points indicated an etripamil treatment effect in terminating PSVT. Etripamil self-administration during PSVT was safe and well tolerated. These results support continued clinical development of etripamil nasal spray for self-administration during PSVT in a medically unsupervised setting. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03464019.